CD86 is linked to apoptosis in canine histiocytic sarcoma - Diehl, Benjamin; Kirchhoff, Andreas; Hansmann, Florian (Frontiers in Veterinary Science, 2025)
Immune checkpoints are critical for the regulation of tumor growth and regression. Recently an effect of CD80 and CD86 on tumor regression in canine cutaneous histiocytoma has been described. Further, the expression of MX dynamin like GTPase 1 (mx1) in cancer is linked to immune evasion. Thus, the present study aimed to investigate the effects of CD80 and CD86 in histiocytic sarcoma (HS), a rare and progressive malignancy in dogs and to elucidate the status of the interferon-I pathway. Twenty-two tissue samples of HS from skin, lung and liver of 15 dogs were used. Immunohistochemistry targeting CD80, CD86, programmed death-ligand 1 (PD-L1), survivin, cleaved caspase-3 (Casp-3), stimulator of interferon genes (STING) and mx1 was performed. Slides were digitized and analyzed with QuPath. The numbers of CD86- and Casp-3 expressing cells showed a positive correlation. In the skin and lung, numbers of CD80 immunolabeled cells were higher than for CD86, while CD80 and CD86 levels were comparable in the liver. In general, low numbers of PD-L1 immunolabeled tumor cells were detected. Intranuclear survivin expression was linked to Casp-3. Mx1 and STING were expressed in tumor cells. A possible link between CD86 and Casp-3 points to a role of CD86 in tumor cell death. The findings indicate relevant differences in CD80 and CD86 expression between organs and a function in histiocytic disease in dogs. Further, the expression of markers of the interferon-type-I pathway indicates a role in immune evasion.